Development of wearable patch antennas using rubber substrate for wban applications - Sakib, Nazmus (Kulliyah of Engineering,International Islamic University Malaysia, 2021)
The flexibility in designing the wearable microstrip patch antenna is essential for Wireless Body Area Network (WBAN) applications. The shortcomings of the wearable antenna are due to variations in characteristics once the dielectric substrate is squeezed or expanded along the outer or inner surface. In bending conditions, the overall performances in flexible antenna could be decreased. Thus, the performance should subsequently improve in designing flexible antennas. This research mainly focused on designing the microstrip patch antennas with rubber substrate as a dielectric material. Computer Simulation Technology (CST) software used for antenna simulation and analysis. We developed four types of antennas on rubber substrate to study their performances in return loss, gain, radiation efficiency, etc. Initially, the microstrip patch antenna was designed with and without defected ground structure (DGS) applied on rubber substrate. Then, we designed a coplanar waveguide (CPW) monopole antenna for single-band and multiband applications. For the DGS antenna, the reflection coefficient of -37.33 dB, the bandwidth of 4.16% (at -10 dB impedance), the antenna gain increased by 7.5%, and the voltage standing wave ratio (VSWR) value was 1.03 with the resonant frequency at the ISM band has been attained. Meanwhile, the CPW antenna reduced the overall antenna thickness (two layers) and achieved single-band and multiband applications at 2.45 GHz and 3.65 GHz. Focusing on antenna bandwidth and radiation efficiency, CPW antenna (single band) achieved the 22.16% bandwidth and around 90% of radiation efficiency. The antenna gain has improved from 3.18 dBi (without DGS) to 4.26 dBi (CPW antenna for multiband). Subsequently, we fabricated the best performance antenna, a CPW antenna for a single band using the screen-printing technique. The return loss obtained from the experiment was -22 dB, slightly different from the simulation. The VSWR value was 1.22, which was almost near to the simulation (at 1.06). This antenna can further improve by enhancing the CPW features.